Sustainable mobility and the US press: the newspaper coverage of electric vehicles (1995-2015). (17th May 2021) - Mangani, Andrea; Pacini, Barbara
Scholars have long debated about the economy-environment trade-off, for which the economic conditions affect the attention of citizens and mass media towards environmental issues. This paper explores this theme within the US press and studies which factors are associated with the media coverage of electric vehicles (EVs) in four major national newspapers between 1995 and 2015. According to the empirical estimates, the media attention towards EVs shows a weak association with good economic conditions, policy initiatives in support of sustainable mobility, and tenures of Democratic presidents.